2017
DOI: 10.1002/bjs.10487
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the role of biomarkers in diagnosing anastomotic leakage following colorectal surgery

Abstract: Peritoneal drain fluid and systemic biomarkers are poor predictors of AL after colorectal surgery. Combinations of these biomarkers showed improvement in predictive accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 69 publications
1
74
0
2
Order By: Relevance
“…CRP was evaluated in a recent systematic review by Su'a et al . who concluded that the CRP level was generally raised significantly days before the clinical diagnosis of AL . The reported cut‐off values for CRP ranged from 94 to 190 mg/l for postoperative days 3–4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CRP was evaluated in a recent systematic review by Su'a et al . who concluded that the CRP level was generally raised significantly days before the clinical diagnosis of AL . The reported cut‐off values for CRP ranged from 94 to 190 mg/l for postoperative days 3–4.…”
Section: Discussionmentioning
confidence: 99%
“…Su'a et al also observed differences in the increase of different biomarkers at different time points during the postoperative period [21]. Whilst this group demonstrated an increase in biomarkers for ischaemia immediately after surgery, the increase in markers for inflammation (e.g.…”
Section: Al Pathophysiologymentioning
confidence: 91%
See 1 more Smart Citation
“…Anastomotic leak (AL) is one of the most dreaded complications following major colorectal surgery. Reported AL rates range from 3% to 27%, and this is associated with significant morbidity and mortality . The early diagnosis of AL is difficult due to its variable clinical course particularly in the early postoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…The early diagnosis of AL is difficult due to its variable clinical course particularly in the early postoperative period. Furthermore, in a modern optimized perioperative care setting, patients may be discharged before clinical features of AL become apparent …”
Section: Introductionmentioning
confidence: 99%